Hubungan Pola Pikir Negatif dengan Stres Akademik pada Mahasiswa Kedokteran - Dyah Ayu Siti Utari Pramasasti; Sri Maria Puji Lestari; Esteria Marhayuni (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2022)
Students life was changes in Covid-19 pandemic, both in learning or in economy aspect. This case can trigger the person to experience academic stress. One of the factors that influence academic stress is mindset. Mindset can more affect a person when facing a problem. The person’s who have negative mindset usually consider themselves incapable so they can prevent a person from getting a better quality of life. The purpose of this research is to find out whether there is a relationship between negative mindset with academic stress in Medical Students of Malahayati University during covid-19 pandemic. This research is a quantitative research with a analytic type. Data sources with questionnaires.The study respondents is 121 students with the most negative mindset levels in the moderate category, which was 78 people (64.5%). And the highest level of academic stress in the weight category amounted to 66 people (54.5%). Statistical  studies show the value of p or p-value is 0.989 (p > 0.05) and the correlation test is  0.001, so it can be concluded that there is no significant association between negative mindset and academic stress in Malahayati University medical students during the Covid-19 pandemic class of 2018. Keywords: Negative Mindset, Academic Stress